2008
DOI: 10.1002/macp.200700398
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Chemical Heterogeneity and the Crystallization Behavior of PP‐g‐PS Graft Copolymers Using SEC‐FTIR and CRYSTAF

Abstract: Graft copolymers of propene with styrene were analyzed with regard to their chemical heterogeneity using both SEC coupled to FT‐IR spectroscopy and CRYSTAF. The SEC‐FTIR indicates chemical homogeneity of the copolymer samples. The decrease in crystallization temperature in CRYSTAF does not correlate with the concentration of PS in the samples but it correlates decisively with the branching frequency. The length of the PS branches does not influence the crystallization temperature in CRYSTAF, although the longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 21 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…They are mainly based on selective precipitation or adsorption mechanisms on different stationary phases. The fast and efficient separation of polyolefins and olefin copolymers with respect to chemical composition in a short time can only be achieved by the above method [39][40][41][42][43][44]. Recently, the use of a graphitic stationary phase (Hypercarb) for the separation of PP according to tacticity was reported [38].…”
Section: Analytical Methods For Polyolefinsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are mainly based on selective precipitation or adsorption mechanisms on different stationary phases. The fast and efficient separation of polyolefins and olefin copolymers with respect to chemical composition in a short time can only be achieved by the above method [39][40][41][42][43][44]. Recently, the use of a graphitic stationary phase (Hypercarb) for the separation of PP according to tacticity was reported [38].…”
Section: Analytical Methods For Polyolefinsmentioning
confidence: 99%
“…These include the SEC-FTIR analysis of ethylene-vinyl acetate (EVA) copolymers [39], ethylene-methyl methacrylate (EMMA) copolymers [40,41], ethylene-styrene copolymers [42], HDPE and PP [43]. These include the SEC-FTIR analysis of ethylene-vinyl acetate (EVA) copolymers [39], ethylene-methyl methacrylate (EMMA) copolymers [40,41], ethylene-styrene copolymers [42], HDPE and PP [43].…”
Section: Branching Analysis By Coupled Sec-ftirmentioning
confidence: 99%
“…Macko et al [64] analyzed graft copolymers of propene and styrene regarding chemical heterogeneity by SEC coupled with FTIR and CRYSTAF. The results showed that the PP-g-PS copolymers have a well defined homogenous graft structure.…”
Section: Crystallization Analysis Fractionationmentioning
confidence: 99%
“…Over the last few years a number of applications on the analysis of olefin copolymers have been published that make use of the LC-Transform system. These include the SEC-FTIR analysis of ethylene/vinyl acetate copolymers [117], ethylene/ methyl methacrylate copolymers [118,119], ethylene/styrene copolymers [120], HDPE and PP [121]. A number of studies used SEC-FTIR for monitoring the thermo-oxidative degradation of polyolefins [122][123][124][125][126] and a combination of TREF and SEC-FTIR to investigate the complex structure of olefin copolymers [127,128].…”
mentioning
confidence: 99%
“…[9] The CCD of polyolefins and functionalized polyolefins is routinely analyzed using Temperature Rising Elution Fractionation (TREF), Crystallization Analysis Fractionation (CRYSTAF) [10][11][12][13][14] or DSC. [15] SEC coupled to FTIR [16][17][18][19][20][21] delivers information about the distribution of comonomer units along the molar mass axis. TREF and CRYSTAF are based on the crystal-lization of macromolecules from a hot solu-tion.…”
Section: Introductionmentioning
confidence: 99%